2006
DOI: 10.1111/j.1572-0241.2006.00458.x
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Double-Blind Placebo-Controlled Trial of Rifaximin in Patients with Abdominal Bloating and Flatulence

Abstract: Rifaximin is a safe and effective treatment for abdominal bloating and flatulence, including in IBS patients. Symptom improvement correlates with reduction in H2-breath excretion. Future trials are needed to examine the efficacy of long-term or cyclic rifaximin in functional colonic disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
226
3
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(244 citation statements)
references
References 28 publications
10
226
3
5
Order By: Relevance
“…Rifaximin, in particular, has generated much interest in recent years [Lembo et al 2008;Ringel et al 2008;Pimentel et al 2006;Sharara et al 2006]. This drug is minimally absorbed providing high luminal bioavailability with few systemic side effects [Scarpignato and Pelosini, 2006].…”
Section: Antibioticsmentioning
confidence: 99%
“…Rifaximin, in particular, has generated much interest in recent years [Lembo et al 2008;Ringel et al 2008;Pimentel et al 2006;Sharara et al 2006]. This drug is minimally absorbed providing high luminal bioavailability with few systemic side effects [Scarpignato and Pelosini, 2006].…”
Section: Antibioticsmentioning
confidence: 99%
“…The rationale underling this drug is that an intestinal dysbiosis could increase gas production. In 2006, Sharara et al [110] demonstrated that a 10 d course of rifaximin is effective in reducing bloating symptoms without significant adverse events. Also, another interesting double blind, randomized, placebo-controlled trial, showed that patients with IBS (based on Rome Ⅰ criteria) treated with rifaximin reported a significant improvement in bloating and IBS symptoms compared to patients who received placebo (p = 0.010) [111] .…”
Section: Treatmentmentioning
confidence: 99%
“…A combination of simethicone plus activated charcoal and magnesium oxide was tested against placebo in a double blind, ran- [136] Ⅱ Lactobacillus plantarum 299v: improvement [137] Ⅲ Multispecies: improvement [138] Ⅲ Symbiotics Symbiotic mixture: no benefits [115,116] Ⅲ Antibiotics Rifaximin: reduction in bloating-specific scores [110] Ⅱ Rifaximin: improvement (39.5% vs 28.7%) [112] Ⅱ Prokinetics Tegaserod: improvement [120] Ⅰ Tegaserod: improvement [139][140][141] Ⅱ Tegaserod: no differences vs placebo [142] Ⅱ Prucalopride: improvement [126] Ⅱ Antispasmodic Otilonium bromide improvement [143] Ⅱ Mebeverine vs Otilonium bromide: improvement significantly achieved by both treatments [144] Ⅱ Antidepressant Paroxetine: no difference vs placebo [145] Ⅰ Citalopram: improvement [146] Ⅱ Fluoxetine: improvement [147] Ⅱ domized, multicenter trial in patients with FD meeting the Rome Ⅲ criteria [134] . This study showed a reductions in the intensity of post-prandial fullness, epigastric pain, epigastric burning and bloating in the active treatment arm compared to placebo [134] .…”
Section: Treatmentmentioning
confidence: 99%
“…In previous studies, normalization of the results of the breath test in IBS patients after antibiotic therapy has been shown to be correlated with a successful response to antibiotic therapy. 86,92,93,96 The predictive value of a positive lactulose breath test has been disappointing, however, in selecting patients who will respond. [97][98][99] In a recent prospective study that used upper-gut aspiration culture for diagnosing SIBO, IBS patients with SIBO had greater symptom alleviation than patients without SIBO (87.5% vs 25%) 1 month after the administration of antibiotics.…”
Section: Antibiotics In Functional Bowel Disordersmentioning
confidence: 99%
“…91 Many previous studies reported that rifaximin treatment in SIBO and IBS patients had significant benefits compared with placebo. 87,[92][93][94] In the 2 largest phase 3 trials involving people with non-constipated IBS (TARGET 1 and 2), treatment with rifaximin 550 mg 3 times a day for 2 weeks achieved adequate alleviation of the global IBS symptoms (40.7% vs 31.7% for placebo, pooled; P < 0.001) and bloating (40.2% vs 30.3% for placebo, pooled; P < 0.001) during the first 4 weeks after treatment. 87 In addition, a Although it is generally acknowledged that rifaximin leads to short-term clinical improvements in some IBS patients, there are several points to be considered before promoting the widespread use of rifaximin.…”
Section: Antibiotics In Functional Bowel Disordersmentioning
confidence: 99%